Student Procedural Fluency in Numerical Method Subjects - Inayah, Sarah; Septian, Ari; Suwarman, Ramdhan Fazrianto (Desimal: Jurnal Matematika, 2020)
This study aims to explain the procedural fluency of students in numerical methods courses. Procedural fluency refers to knowledge of procedures, about when and how to use them appropriately, and the skills to carry out procedures flexibly, accurately, and efficiently. The method in this study uses a descriptive method with a qualitative approach and data analysis techniques for the Miles and Huberman models. In this study also performed triangulation of techniques by conducting interviews to strengthen the test result data. From the data analysis, it can be concluded that regarding the smoothness in students' procedural procedures in solving problems related to numerical methods courses, students are able to solve problems with more than one method. However, some students have not been able to streamline steps and make accurate calculations. In addition, mastery in operating a scientific calculator needs to be improved so that students can be more efficient and get more accurate answers.